Love Unique Music Corporation / Micellinus Manuil... [et al.] - Ukol, Cdarleen; Simar, Vivi Adrianti; Juning, Norsafikah; Abdullah, Nurazreen Munira; Manuil, Micellinus (2014)
The name of our business is Love Unique Music Corporation. This business is one of service type of business. This business is services about organizing a party. People may call us the party organizer. However, our customer may call us the Love Unique Music (LUMc). Our main target is to make every customer enjoy their life with the music. The idea of the formation of this business is basically and entirely by my team member passions and dedications. The team member consists of five people including myself. Our target market for now is only at Kata Kinabalu area. After the development of our business, only then we will expand this ideology throughout the country. Love Unique Music is focus entirely on organizing Jazz music.